The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1097/inf.0b013e318235c7aa
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Congenital Anomalies in Infants With In Utero Exposure to Antiretrovirals

Abstract: Background While use of efficacious interventions, including antiretrovirals (ARVs), has reduced dramatically the rate of mother-to-child transmission (MTCT) of HIV, the safety of in utero ARV exposure remains of concern. Methods Data regarding 1112 infants enrolled in the International Maternal Pediatric Adolescent AIDS Clinical Trials Group (IMPAACT) protocol P1025 born between 2002 and 2007 were analyzed for this study. Congenital anomalies were classified based on the Metropolitan Atlanta Congenital Defe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
2
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 26 publications
3
54
2
1
Order By: Relevance
“…[5][6][7][8][9][17][18][19] The reasons underlying this variability may include the variable definition of birth defects, underreporting, the selective reporting of cases with defects, differential use of diagnostic techniques in the ascertainment of defects, and variable concomitant medication and substance exposure. 19 We also evaluated other potential predictors of birth defects, such as age, recent substance use, time since HIV diagnosis, CD4 cell count, body mass index, and coinfections. Overall, as for other studies in HIV infection, no maternal risk factors for birth defects were identified.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9][17][18][19] The reasons underlying this variability may include the variable definition of birth defects, underreporting, the selective reporting of cases with defects, differential use of diagnostic techniques in the ascertainment of defects, and variable concomitant medication and substance exposure. 19 We also evaluated other potential predictors of birth defects, such as age, recent substance use, time since HIV diagnosis, CD4 cell count, body mass index, and coinfections. Overall, as for other studies in HIV infection, no maternal risk factors for birth defects were identified.…”
Section: Discussionmentioning
confidence: 99%
“…But, it was also found several medications which might cause congenital anomaly in other studies such as NSAID. 6 NSAID might cause cleft lip, spine anomaly, and others. 6 Antiretroviral consumption might also cause congenital anomaly.…”
Section: Resultsmentioning
confidence: 99%
“…6 NSAID might cause cleft lip, spine anomaly, and others. 6 Antiretroviral consumption might also cause congenital anomaly. 7 However, there are several medications which might prevent congenital anomaly prevalence, for example, folic acid consumption in pre-conception time.…”
Section: Resultsmentioning
confidence: 99%
“…Chez la femme, les données sont encore discordantes : après la description de quelques cas cliniques d'anomalies neurologiques, la méta-analyse d'une série de cohortes et d'un registre déclaratif américain suggère l'absence de risque [10]. Plus récemment, deux cohortes -dont la cohorte EPF-ANRS -démentent toutefois cette analyse et retrouvent un risque significatif [11,12]. Ces doutes doivent être levés rapidement.…”
Section: Risques D'embryofoetopathieunclassified